(untitled) (Research, Society and Development, 2025)
Introduction: Nursing care in the prevention of foot ulcers in diabetic patients, including self-care education and regular inspection, is crucial to reduce complications, improve quality of life and mental health. Objective: To analyze the factors that contribute to care in the development of foot ulcers in diabetic patients, directing the identification of guidelines that can reduce the risk and improve nursing care. Methodology: A qualitative and exploratory systematic review was carried out through the Google Scholar, SciELO and PubMed platforms, limited to studies published between 2019 and 2024, with 8 articles selected at the end. Results: Nursing plays a crucial role in the prevention of diabetic foot, focusing on continuous assessment of the feet, health education and glycemic control. Discussion: Strategies such as home visits, self-care guidance and family involvement help prevent serious complications, such as ulcers and amputations. Continuous training of nursing professionals is essential to improve clinical practice and outcomes. Conclusion: Nursing plays an essential role in the prevention of diabetic foot, promoting self-care, glycemic control and education. Strategies such as home visits and ongoing training are essential to reduce complications and amputations.